PERBANDINGAN GRAMATIKA TATA BAHASA BAKU BAHASA INDONESIA EDISI PERTAMA DAN EDISI KETIGA - Miftahul Huda (Pendidikan Bahasa dan Sastra Indonesia, 2017)
The language change could occur at all levels, both phonology, morphology, syntax, semantics, and lexicon. It showed that it is possible to change the language that is the case, the book of grammar will also continue to change according to the changes, hence the old grammar book (TBBBI I) should be less relevant for use again, especially with the book grammar new (TBBBI III) , Based on these issues, this study aimed to describe (1) the grammar in the book TBBBI at the first edition, (2) the grammar in the book of TBBBI at the third edition, (3) the similarities and differences in grammar book TBBBI at the first and the third edition. The method used in this study was a descriptive qualitative research method. Based on the survey results revealed that the two books TBBBI, namely TBBBI I and III of this can be seen that there are similarities and some differences in the content, there are also additional rules (sub theme) which is not found in TBBBI I which shows that language is always evolving. In addition, the change in the name of prefix, the allomorph menge-, classification of transitive and intransitive verbs showes that TBBBI III more relevant to read than TBBBI I.